Metrnl inhibits choroidal neovascularization by attenuating the choroidal inflammation via inactivating the UCHL-1/NF-κB signaling pathway - Zhang, Lanyue; Li, Youjian; Wu, Zhengyu; Shen, Qiang; Zeng, Chunqin; Liu, Han; Zhang, Xuedong; Yang, Jiaxing; Liu, Qiaoling; Tang, Dianyong; Ou, Kepeng; Fang, Yanhong (Frontiers in Immunology, 2024)
Objective: Choroidal neovascularization (CNV) represents the predominant form of advanced wet Age-related Macular Degeneration (wAMD). Macrophages play a pivotal role in the pathological progression of CNV. Meteorin-like (Metrnl), a novel cytokine known for its anti-inflammatory properties in macrophages, is the focus of our investigation into its mechanism of action and its potential to impede CNV progression.Methods: Cell viability was evaluated through CCK-8 and EdU assays following Metrnl treatment. Expression levels of inflammatory cytokines and proteins were assessed using quantitative reverse-transcription polymerase chain reaction(qRT-PCR), enzyme-linked immunosorbent assay(ELISA), and western blot techniques.Protein-protein interactions were identified through protein mass spectrometry and co-immunoprecipitation(Co-IP). Additionally, in vivo and in vitro neovascularization models were employed to evaluate angiogenesis.Our results revealed downregulated Metrnl levels in the choroid-sclera complex of CNV mice, the aqueous humor of wAMD patients, and activated macrophages. Metrnl overexpression demonstrated a reduction in pro-inflammatory cytokine production, influenced endothelial cell function, and suppressed angiogenesis in choroid explants and CNV models. Through protein mass spectrometry and Co-IP, we confirmed Metrnl binds to UCHL-1 to modulate the NF-κB signaling pathway. This interaction inhibited the transcription and expression of pro-inflammatory cytokines, ultimately suppressing angiogenesis. .In summary, our findings indicate that Metrnl down-regulates macrophage pro-inflammatory cytokine secretion via the UCHL-1/NF-κB signaling pathway. This mechanism alleviates the inflammatory microenvironment and effectively inhibits choroidal neovascularization.